O impacto da forma de contratação no custo da mão de obra - Sgarbossa, Ricardo (2019)
The construction sector is one of the engines of the economy of the country, and its products are highly dependent on labor, and that your time has big share in costs related to the construction process. In this sense, companies began to seek ways to minimize the cost of workers, by means of outsourcing of services or strategies to increase the productivity of the workforce itself. The aim of this study was to compare the costs of different forms of contract labour. To do this, we conducted a case study applied to a hypothetical residential condominium, composed of eight 54 residences, 88 m ², from which three simulations were performed in order to obtain the cost for hiring labor, contract global and per task. The value for first simulation was obtained from the schedule of work, through which determined the number of teams and the time of execution of the work, which served as parameters for determining the cost of payroll. Already the cost to global contract job, was obtained from quotes made with contractors, who provided the total amount collected for execution. Finally, the cost for hiring by task was obtained from the quotations of certain services, along with a detailed budget held the TCPO and SINAPI. The results show that the cost for hiring of labour for global enterprise presented a 105.315% lower cost than the cost of hiring labor, 28.62% lower and that hiring by task. However, points out that during the recruitment of the global contract job, can occur from the contractor not to count on labor, so as not to collect taxes, so harmful to workers, who are destitute of benefits assets.